Does income inequality lead to consumption inequality? Evidence and theory - Dirk Krueger; Fabrizio Perri (Goethe University Frankfurt, Center for Financial Studies (CFS), 2005)
Using data from the Consumer Expenditure Survey we first document that the recent increase in income inequality in the US has not been accompanied by a corresponding rise in consumption inequality. Much of this divergence is due to different trends in within-group inequality, which has increased significantly for income but little for consumption. We then develop a simple framework that allows us to analytically characterize how within-group income inequality affects consumption inequality in a world in which agents can trade a full set of contingent consumption claims, subject to endogenous constraints emanating from the limited enforcement of intertemporal contracts (as in Kehoe and Levine, 1993). Finally, we quantitatively evaluate, in the context of a calibrated general equilibrium production economy, whether this set-up, or alternatively a standard incomplete markets model (as in Ayiagari 1994), can account for the documented stylized consumption inequality facts from the US data.
urn:nbn:de:hebis:30-10912
Keywords: E21; D91; D63; D31; G22; 330; Limited Enforcement; Risk Sharing; Consumption Inequality; Einkommensverteilung; Gesamtwirtschaftlicher Konsum; Theorie; USA